Clinical Applications of Optical Coherence Tomography in Ophthalmology - Masoud Aghsaei Fard (مجله دانشگاه علوم پزشکی گیلان)
I read the study conducted by Alizade et al. [1] which was interesting. I need to indicate some points about the use of Optical Coherence Tomography (OCT) in ophthalmology and optic nerve diseases. As Alizadeh et al. [1] stated, OCT has become popular for the diagnosis and follow-up of retinal and optic nerve diseases due to its high reproducibility. In this letter, I discuss the role of OCT in optic nerve ischemia and share my experiences in this field. Then, I review the role of OCT angiography (OCT-A) and recent developments in this field, as well as the role of artificial intelligence in ophthalmology.